Faktor Yang Mempengaruhi Tax Avoidance Perusahaan Property Dan Real Estate - Christian, Jamaludin Iskak (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to determine the effect of independent variables consisting of leverage, profitability, sales growth, company size, and capital intensity on dependent variable tax avoidance. The sample used in this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period of 2016-2018. The method for sampling is purposive sampling in order to obtain 38 companies. Data processing for this research used EViews 10 software. Tests used to obtain the model are Chow test and Hausman test. The best model used after conducting the test is Random Effect Model (REM). So the results of this research is leverage and profitability affect tax avoidance, while sales growth, company size, and capital intensity do not affect tax avoidance.